2021
DOI: 10.1177/00938548211014234
|View full text |Cite
|
Sign up to set email alerts
|

Criminogenic Need Profiles Among Substance-Using Justice-Involved Youth

Abstract: The relationship between juvenile offending and substance use is well-documented. Understanding this relationship in the context of other criminogenic needs could lead to more effective treatment programming, in an effort to reduce future justice system involvement. This study retrospectively classified 276 substance-using youth in the justice system into unique profiles based on the nature and severity of self-reported substance use and criminogenic needs. We tested competing latent profile analysis (LPA) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Yet, the class characterized by high polysubstance use of alcohol, marijuana, and other drugs had significantly greater externalizing symptoms, problems related to substance use, adverse family living situations, and social relationships. A similar study was conducted with Canadian youth (aged 12–20) with justice involvement [30 ▪▪ ]. This study found four latent subgroups of substance use and criminogenic needs; the polysubstance use latent profile had a higher proportion of individuals with ADHD, and half of the youth recidivated within 3 years of release, comparable to youth in the other latent profile groups [30 ▪▪ ].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Yet, the class characterized by high polysubstance use of alcohol, marijuana, and other drugs had significantly greater externalizing symptoms, problems related to substance use, adverse family living situations, and social relationships. A similar study was conducted with Canadian youth (aged 12–20) with justice involvement [30 ▪▪ ]. This study found four latent subgroups of substance use and criminogenic needs; the polysubstance use latent profile had a higher proportion of individuals with ADHD, and half of the youth recidivated within 3 years of release, comparable to youth in the other latent profile groups [30 ▪▪ ].…”
Section: Introductionmentioning
confidence: 61%
“…A similar study was conducted with Canadian youth (aged 12–20) with justice involvement [30 ▪▪ ]. This study found four latent subgroups of substance use and criminogenic needs; the polysubstance use latent profile had a higher proportion of individuals with ADHD, and half of the youth recidivated within 3 years of release, comparable to youth in the other latent profile groups [30 ▪▪ ].…”
Section: Introductionmentioning
confidence: 61%
“…In contrast, the DAST-A did not predict reoffending in Black youth or meaningfully in young men or women as separate subgroups. De Somma et al (2021) identified different profiles among justice-involved youth who abuse substances. In a group with clinical drug use and low-to-moderate criminogenic needs, almost half the youth were Black, while less than a quarter were White.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…It is a fact that there is a strong social component to antisocial behavior in adolescence (Xu et al, 2020), and that these acts are more likely to occur in groups (Sijtsema & Lindenberg, 2018). Peer pressure has been hypothesized to be an important contributor to deviant and risky behaviors in adolescence, as minor delinquency, serious offending, reckless driving, and drug and alcohol use (De Somma et al, 2021;Yoon, 2020). Taking into account The Big Four Model and the results obtained by Cuervo et al (2017a, b, c), the presence of antisocial peer relationships is among the strongest predictors of recidivism, as these antisocial relationships can influence negatively on the decisions adolescents make when having the opportunity to engage in infringing acts.…”
Section: Risk Factors For Child-to-parent Violencementioning
confidence: 99%